A catalogue of high-mass X-ray binaries in the Galaxy: from the INTEGRAL to the Gaia era, - Fortin, Francis (2023)
Context. High-mass X-ray binaries (HMXBs) are a particular class of high-energy sources that require multi-wavelength observational efforts to be properly characterised. New identifications and the refinement of previous measurements are regularly published in the literature by independent teams of researchers and might, when they are collected in a catalogue, offer a tool for facilitating further studies of HMXBs.Aims. We update previous instances of HMXB catalogues in the Galaxy and provide the community easy access to the most complete set of observables on Galactic HMXBs. In addition to the fixed version that is available in Vizier, we also aim to host and maintain a dynamic version that can be updated upon request from users. Any modification will be logged in this version.Methods. Using previous HMXB catalogues supplemented by listings of hard X-ray sources detected in the past 20 yr, we produced a base set of HMXBs and candidates by means of identifier and sky coordinate cross matches. We queried in Simbad for unreferenced HMXBs. We searched for as many hard X-ray, soft X-ray, optical, and infrared counterparts to the HMXBs as we could in well-known catalogues and compiled their coordinates. Each HMXB was subjected to a meticulous search in the literature to find relevant measurements and the original reference.Results. We provide a catalogue of 152 HMXBs in the Galaxy with their best known coordinates, the spectral type of the companion star, systemic radial velocities, component masses, orbital period, eccentricity, and spin period when available. We also provide the coordinates and identifiers for each counterpart we found from hard X-rays to the near-infrared, including 111 counterparts from the recent Gaia DR3 catalogue.